The “chameleon” sellar lesions: a case report of unexpected sellar lesions - Bove, Ilaria; Franca, Raduan Ahmed; Ugga, Lorenzo; Solari, Domenico; Elefante, Andrea; De Caro, Maria Laura Del Basso; Cavallo, Luigi Maria (Frontiers in Neurology, 2023)
Introduction The sellar and the suprasellar regions represent very complex areas, harboring a remarkable variety of tissues of different lining, so that many diseases can arise or involve these areas, with the most majority from hypophysis, both neoplastic or not. We report three challenging cases of “chameleon” sellar lesions treated via EEA that mimicked radiological features of common lesions such as craniopharyngiomas and/or pituitary adenomas, with literature review of similar cases. Methods A retrospective analysis of three primary cases was conducted at a single institutions Università degli Studi di Napoli Federico II, Naples, Italy. Clinical charts, operative notes, and pathology reports were examined. Results Three cases of “chameleon” sellar lesions included two men and one woman. Based on the intraoperative finding and pathological examination, we noticed that case 1 had suprasellar glioblastoma, case 2 had primary neuroendocrine tumor, case 3 had cavernous malformation. Conclusion Neurosurgeons should consider “unexpected” lesions of the sellar / suprasellar region in the preoperative differential diagnosis. The multidisciplinary approach with the collaboration of neurosurgeons, neuroradiologists and pathologists plays a fundamental role. The rapid definition of the lesion can help surgeons for a better preoperative planning, and in this scenario the endonasal endoscopic approach could be fundamental to obtain the decompression of the neurovascular structures and the pathological diagnosis, with less morbidity.